2019
DOI: 10.1097/aln.0000000000002847
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxemia, Bradycardia, and Multiple Laryngoscopy Attempts during Anesthetic Induction in Infants

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background The infant airway is particularly vulnerable to trauma from repeated laryngoscopy attempts. Complications associated with elective tracheal intubations in anesthetized infants may be underappreciated. We conducted this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 17 publications
2
30
1
2
Order By: Relevance
“…Patients with airway bleeding did not have an increased requirement for the DART; however, bleeding was not quantified and was likely minimal in these patients. In contrast to literature identifying age less than one year as a risk factor for difficult intubation by anesthesia providers in the OR [2,11,12], our study showed that this age group did not need the DART more frequently than other age groups. This finding is more consistent with results from Graciano et al [3], who showed in univariate analysis that age < 2 years was associated with difficult intubation.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with airway bleeding did not have an increased requirement for the DART; however, bleeding was not quantified and was likely minimal in these patients. In contrast to literature identifying age less than one year as a risk factor for difficult intubation by anesthesia providers in the OR [2,11,12], our study showed that this age group did not need the DART more frequently than other age groups. This finding is more consistent with results from Graciano et al [3], who showed in univariate analysis that age < 2 years was associated with difficult intubation.…”
Section: Discussioncontrasting
confidence: 99%
“…Tracheal intubation particularly in small children is a challenging procedure and successful tracheal tube insertion through the vocal cords should entail both a gentle laryngeal passage and a sufficient tracheal seal, once inflated . A too small tracheal tube cuff results in air leak with all the disadvantages of an unsealed tracheal airway; namely, an absent endtidal CO 2 signal in spite of correct tracheal intubation, imprecise endtidal‐CO 2 monitoring, impaired ventilation and oxygenation, environmental pollution with anesthetic gases with increased gas consumption and ultimately the risk of tube exchange, as is known from uncuffed tracheal tubes .…”
Section: Discussionmentioning
confidence: 99%
“… Stinson et al 2018 166 1,448 Hospitalized pediatric patients Failure of intubation or SGA insertion on 1st attempt associated with progression of acute respiratory compromise to cardiac arrest (OR, 1.8; 95% CI, 1.2 to 2.6). Gálvez et al 2019 186 1,341 Infants: Operating room and diagnostic imaging 2 or more attempts associated with increased odds ratio of SpO 2 < 90% for at least one minute (OR, 1.78; 95% CI, 1.3 to 2.4). Amalric et al 2020 187 202 Critical care Complications occurred in 11% of those intubated on the first attempt; 32% with > 2 attempts ( P < 0.001).…”
Section: Response To An Unsuccessful First (Or Subsequent) Attempt At the Intended Airway Techniquementioning
confidence: 99%